Ensuring Construction Workers Legal Protection: A Legal Analysis of Construction Competency Certificates under the Law on Personal Data Protection and Blockchain Frameworks - Afrilies, Marlia Hafny; Lina, Angie Angel; Theresia, Maria; Simanjuntak, Efendi; Naili, Yuris Tri; Garunja, Evis; Mohd Aboobaider, Burhanuddin bin (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
National development towards Indonesia 2045 is massively carried out, based on the Coordinating Minister for Economic Affairs Regulation Number 21 of 2022 that Indonesia has 210 development projects and 12 programs, in December 2022 a total of 152 projects have been implemented and are fully operational. Realizing national development, Construction Service Business Entities require Construction Workers to certify so that the quality and qualifications of the workforce can be recognized and professional accountability is formally clear. However, the security of the professional certificate of construction services is not guaranteed. The research uses normative juridical methods by examining all regulations related to the issues discussed. Determining the qualifications of construction service business entities that are assessed, one of which is the availability of construction labor. The procedures and flow of procedures for implementing construction work competency certificates are regulated in the Regulation of the Minister of Public Works and Public Housing Number 8 of 2022 concerning Procedures for Implementing the Fulfillment of Construction Service Standard Certificates in order to support the ease of business licensing for construction service business actors. Repressive efforts in cybercrime are guaranteed by Law No. 27 of 2022 on Personal Data Protection. To prevent cybercrime in the LPJK data storage system, it can cooperate with the Ministry of Communication and Information Technology regarding the policy of using Blockchain.